Development Strategy of Human Resource Management For Millennial Generation - Novi Febriyanti; A. Fikri Amiruddin Ihsani (AFEBI Management and Business Review, 2019)
Development strategy of human resource management for millennial generation is a step purposed at producing superior individuals who have characteristics and abilities that can compete and have a sale value that can be relied on either in a company or organization. The purposes of this study was to answering the formulation of problems regarding the characteristics of millennial generation related to work culture and human resource development strategies for millennial generation. The research method used descriptive qualitative by library research or literature study. The results of this study prove that the strategy being carried out is a way to improve the ability of every individual likes a training responsibility, intensive learning, behavior modification, immediate information, learning practice and patterns. Supporting sustainable factors are ability, motivation and opportunity.